2017
DOI: 10.1186/s12884-017-1416-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of barriers and facilitators for optimal cesarean section care: perspective of professionals

Abstract: BackgroundThe cesarean section (CS) rate has increased over recent decades with poor guideline adherence as a possible cause. The objective of this study was to explore barriers and facilitators for delivering optimal care as described in clinical practice guidelines.MethodsKey recommendations from evidence-based guidelines were used as a base to explore barriers and facilitators for delivering optimal CS care in The Netherlands. Both focus group and telephone interviews among 29 different obstetrical professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
1
23
1
Order By: Relevance
“…The study has denied that experience of the anesthetists had no association with DDI. In contrast to our finding, there is a study that showed lack of experience of the obstetricians, anesthetists and hesitation of the pregnant mother to give consent can be barriers to achieve shorter DDI [25].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The study has denied that experience of the anesthetists had no association with DDI. In contrast to our finding, there is a study that showed lack of experience of the obstetricians, anesthetists and hesitation of the pregnant mother to give consent can be barriers to achieve shorter DDI [25].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, time to collect surgical materials had a positive association with prolonged DDI in category-1 emergency C/S(AOR =, CI =, p=).This is consistent with a research done by Tak Yeung Leung et al which has stated that a DDI below 30 min was achievable if the operation facilities were easily available [24]. Another study has showed that lack of surgical equipments was the main factor for prolonged DDI time [25]. A DDI below 30 min was difficult to attain in emergency C/S due to the infrastructural challenges [23].…”
Section: Discussionsupporting
confidence: 90%
“…Three Chinese-language articles44–46 were assessed following translation into English by a native Chinese speaker. An additional two papers were identified after the completion of this screening process—one was included47 and one was excluded 48…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies have reported barriers to accessing Csections as inadequate skilled human resources (medical doctors, gynaecologists, obstetricians, anaesthetists and midwives), 9,10,11 equipment, 12,13,14 commodities, 15 infrastructure, 11,16 delays in accessing services and failure to follow policies and guidelines on quality of C-section care. 13 Tanzania, with an estimated population of 58.4 million, 17 is one of the top 10 countries that contribute to 58% of the global maternal mortality.…”
Section: Essential Supplies Including Blood and Medicinesmentioning
confidence: 99%